DAMPAK PANDEMI COVID-19 TERHADAP PENGEMBANGAN AGROWISATA BONJERUK LOMBOK TENGAH - Fitriana Fitriana; Ibrahim Irzan (Kepariwisataan: Jurnal Ilmiah, 2022)
Behind the Sade Tourism Village which has been famous throughout the world, there are also other Tourism Villages that can also be visited by tourists, one of which will be discussed, namely the Bonjeruk Tourism Village, which is a village that still adheres to the customs of the Sasak Tribe which is also known as a historic village. During the colonial period, Bonjeruk was once the Center for the Government of the Dutch East Indies. The data analysis used in this study is qualitative and uses a SWOT analysis. The SWOT analysis considers internal factors such as strengths and weaknesses, as well as the external environment in the form of opportunities and threats. The research results show that: (1) Bonjeruk Tourism Village is one of the most popular Agro-tourism Destinations in Central Lombok Regency (2) Desa WIsata Bonjeruk is managed by the government, namely the Tourism Office of Central Lombok Regency. The adaptation of new habits is to design recovery strategies and improve the cleanliness of the surrounding environment and campaign for Health Protocols to reduce the spread of the Covid 19 outbreak.